2013
DOI: 10.1556/imas.5.2013.1.4
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal outcomes of idiopathic polyhydramnios

Abstract: Although perinatal outcomes are conflicting in literature, idiopathic polyhydramnios warrants close surveillance especially near term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
10
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 18 publications
3
10
0
2
Order By: Relevance
“…Perinatal mortality was 2 to 5 times higher for neonates after pregnancies complicated with idiopathic polyhydramnios compared with the general population. 3,[9][10][11] Nevertheless, data regarding the long-and short-term outcomes of children from pregnancies with polyhydramnios and normal detailed ultrasound examination is limited due to several considerations. First, much of the data is based on studies from 20 years ago, when sonographic assessment and fetal and neonatal management were less developed.…”
mentioning
confidence: 99%
“…Perinatal mortality was 2 to 5 times higher for neonates after pregnancies complicated with idiopathic polyhydramnios compared with the general population. 3,[9][10][11] Nevertheless, data regarding the long-and short-term outcomes of children from pregnancies with polyhydramnios and normal detailed ultrasound examination is limited due to several considerations. First, much of the data is based on studies from 20 years ago, when sonographic assessment and fetal and neonatal management were less developed.…”
mentioning
confidence: 99%
“…However, our study had a limitation that follow up postnatally was just maintained for one month and 15 neonates were lost to follow up. In another study by Taskin et al, a significantly higher preterm labors and low 1-and 5-min APGAR scores were noted in the idiopathic polyhydramnios group compared with the control group, and they concluded that although perinatal outcomes are conflicting in the literature, idiopathic polyhydramnios warrants close surveillance especially near term [10].…”
Section: Discussionmentioning
confidence: 97%
“…Nevertheless, the study of Taskin et al (25) which examined prenatal outcomes in patients with idiopathic polyhydramnios (59 singleton pregnancies), indicated that the percentage of preterm delivery was higher and average Apgar score was lower in comparison with the control group.…”
Section: Discussionmentioning
confidence: 99%